What do we need to know about speciation? - Butlin, Roger; Debelle, Allan; Kerth, Claudius; Snook, Rhonda R; Beukeboom, Leo W; Castillo Cajas, Ruth F; Diao, Wenwen; Maan, Martine E; Paolucci, Silvia; Weissing, Franz J; van de Zande, Louis; Hoikkala, Anneli; et al. (Trends in ecology & evolution (Amsterdam), 2012)
Speciation has been a major focus of evolutionary biology research in recent years, with many important advances. However, some of the traditional organising principles of the subject area no longer provide a satisfactory framework, such as the classification of speciation mechanisms by geographical context into allopatric, parapatric and sympatry classes. Therefore, we have asked where speciation research should be directed in the coming years. Here, we present a distillation of questions about the mechanisms of speciation, the genetic basis of speciation and the relationship between speciation and diversity. Our list of topics is not exhaustive; rather we aim to promote discussion on research priorities and on the common themes that underlie disparate speciation processes.